Ekfraza v poeziji Gregorja Strniše - Gawlak, Monika (Slavistična revija, 2013)
The poetry of Gregor Strniša undoubtedly constitutes an expression of belief in the coexistence and mutual correspondence of multiple dimensions of the world. Thus the concept of intertextuality seems to be particularly important in the exposition of both the visible and the hidden relations that connect various works of art. The purpose of the following paper is to analyse the intertextual relations arising between the poetry of Strniša and the works of Giorgio de Chirico, a prominent Italian painter, the father of the so-called metaphysical school of painting. Poems from two of Strniša's cycles (Sence and Stolpi), found in the collection entitled Škarje, can be treated as instances of ekphrasis, because they contain direct references pertaining to particular works of de Chirico.
Keywords: "Škarje"; intertekstualnost; intertextuality; nadrealizem; Slovene literature; Slovene literture; Slovene poetry; Slovene poets; slovenska književnost; slovenska poezija; slovenski pesniki; Strniša, Gregor, 1930-1987; surrealism